Prevalence of Refractive Errors in a Multiethnic Asian Population: The Singapore Epidemiology of Eye Disease Study - Pan, Chen-Wei; Zheng, Ying-Feng; Anuar, Ainur Rahman; Chew, Merwyn; Gazzard, Gus; Aung, Tin; Cheng, Ching-Yu; Wong, Tien Y.; Saw, Seang-Mei (Investigative ophthalmology & visual science, 2013)
To determine the prevalence of refractive errors in a multiethnic Asian population aged over 40 years and to examine secular trends and racial differences. A total of 10,033 adults (3353 Chinese, 3400 Indians, and 3280 Malays) participated in this study. Refractive error was determined by subjective refraction. Ocular biometric parameters were determined by partial coherence interferometry. Myopia and high myopia were defined as spherical equivalent (SE) of less than -0.5 diopters (D) and -5.0 D, respectively. Hyperopia was defined as SE of more than 0.5 D. Astigmatism was defined as cylinders less than -0.5 D. The prevalence of myopia, high myopia, hyperopia and astigmatism in Singapore adults aged over 40 years was 38.9% (95% confidence interval [CI] 37.1, 40.6); 8.4% (95% CI 8.0, 8.9); 31.5% (95% 30.5, 32.5); and 58.8% (95% CI 57.8, 59.9), respectively. Compared with the Tanjong Pagar Survey 12 years ago, there was a significant increase in the prevalence of astigmatism and mean axial length (AL) in Chinese adults aged over 40 years in Singapore. Chinese were most likely to be affected by myopia, high myopia, astigmatism, and had the longest AL among the three racial groups. The prevalence of myopia in Singapore adults is lower compared with the younger "myopia" generation in Singapore. The prevalence of astigmatism and mean AL have been increasing significantly within the past 12 years in the Chinese population. Chinese adults had higher prevalence of myopia, high myopia, astigmatism, as well as the longer AL compared with non-Chinese adults in Singapore.